2007
DOI: 10.1179/135100007x200281
|View full text |Cite
|
Sign up to set email alerts
|

Time course and attenuation of ischaemia-reperfusion induced oxidative injury by propofol in human renal transplantation

Abstract: Ischaemia-reperfusion injury resulting from interruption and restoration of blood flow might be related to free radical mediated oxidative stress and inflammation, and subsequently to post-surgery related complications. We studied the impact of renal transplantation on oxidative stress and inflammation by measuring F(2)-isoprostanes and prostaglandin F(2alpha), respectively, during transplantation and post-surgery. Additionally, due to earlier observations, two dissimilar anaesthetic agents (thiopentone and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Propofol protected cells from apoptosis by inhibiting oxidative stress and the corresponding downstream pathways, such as mitochondrial stress [54]. Propofol may counteract oxidative stress by lowering the formation of F(2)-isoprostane, a marker of oxidative stress, during transplantation and post-surgery [55]. Propofol also modulates systemic inflammation resulting from IR by decreasing the expression of nuclear factor-κB, a nuclear transcription factor that plays a key role in oxidative stress (Fig.…”
Section: General Anesthesiamentioning
confidence: 99%
“…Propofol protected cells from apoptosis by inhibiting oxidative stress and the corresponding downstream pathways, such as mitochondrial stress [54]. Propofol may counteract oxidative stress by lowering the formation of F(2)-isoprostane, a marker of oxidative stress, during transplantation and post-surgery [55]. Propofol also modulates systemic inflammation resulting from IR by decreasing the expression of nuclear factor-κB, a nuclear transcription factor that plays a key role in oxidative stress (Fig.…”
Section: General Anesthesiamentioning
confidence: 99%
“…They also reported in the same study; thiopental decreases the kidney I/R damage via free oxygen radicals in rats, and this effect is significant compared to etomidate [13] . Basu et al [23] studied oxidative stres after renal transplantation and inflamatory response and they compared propofol and thiopental. As a result they reported that propofol depressed the inflamatory response [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Basu et al [23] studied oxidative stres after renal transplantation and inflamatory response and they compared propofol and thiopental. As a result they reported that propofol depressed the inflamatory response [23] . The Protective Effect of ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of several clinical trials are eagerly awaited. Propofol is another anaesthetic agent that may reduce I/R injury [161,162]. Experimental models have highlighted the anti-oxidant and anti-apoptotic properties of the agent [161,162].…”
Section: Experimental Agentsmentioning
confidence: 99%